DEVELOPMENT OF AUGMENTED REALITY (AR) BASED THEMATIC POSTER CULTURAL HERITAGE BANDAR SENAPELAN ON LEARNING HISTORY - Suroyo, Suroyo; Putra, Bima Maulana; Al Fikri, Yanuar; Fareza, Meizy; Yuliantoro, Yuliantoro (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study focuses on the development of an Augmented Reality (AR) based thematic poster on the cultural heritage of Bandar Senapelan for history education. The study aims to investigate the effectiveness of AR technology in promoting learners' interest, engagement, and understanding of the cultural heritage of Bandar Senapelan. The study follows a qualitative descriptive research method with a Research and Development (R&D) approach. This research uses two stages, namely the development stage and the implementation stage. 1) Choosing the research theme 2) Literature study on augmented reality, thematic posters, and history learning 3) Product design in the form of augmented reality based on thematic posters of Bandar Senapelan cultural heritage on history learning 4) Validation by history material experts and technology experts 5) Product testing. The visual appeal and accuracy of information presented in the AR-based poster were found to be significant factors contributing to learners' engagement. Moreover, the pilot test demonstrated that the quality of AR-based poster images and audio narration played an essential role in learners' retention of historical knowledge. The AR technology also offered an immersive and interactive learning experience, providing learners with the opportunity to explore Bandar Senapelan's heritage sites virtually. The results suggest that the AR-based thematic poster could be an effective tool for promoting learners' understanding and appreciation of the cultural heritage of Bandar Senapelan. However, the study identified several limitations related to the accessibility, sustainability, and capacity building for implementing AR-based posters. Based on the findings, the study recommends collaboration with stakeholders, capacity building, continuous evaluation, inclusive design, and long-term preservation strategies to promote sustainable use of AR technology in historical education. The study's findings can inform future research and development of AR-based educational resources for promoting historical learning and cultural heritage preservation.